Well-connected microzones for increased building efficiency and occupant comfort - Michael P Andersen; Gabe Fierro; Sam Kumar; Michael Chen; Leonard Truong; Joyce Kim; Edward A Arens; Hui Zhang; Paul Raftery; David E Culler (2nd ACM International Conference on Embedded Systems for Energy-Efficient Built Environments, 2015)
Personal Comfort Systems (PCS) are capable of maintaining occupant comfort in buildings despite large deviations from recommended "comfortable" temperatures. We present a novel digital controller for a well-studied (previously analog) PCS, allowing it to report real-time telemetry and respond to programmatic actuation requests. This enables the established capabilities of a PCS to be synergistically combined with occupant-aware building applications, providing new methods of comfort and energy efficiency maximization.